2020
DOI: 10.1177/0886260520912582
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Maltreatment, Automatic Negative Thoughts, and Resilience: The Protective Roles of Culture and Genes

Abstract: Resilience, a psychological trait conceptualized as the ability to recover from setbacks, can be weakened by childhood maltreatment, which comprises childhood abuse and childhood neglect. The current study aimed to investigate whether childhood maltreatment could increase automatic negative thoughts (ANT), thus weakening resilience. Furthermore, as psychological characteristics are commonly subject to the moderating effects of cultural context and biology, the study also explored whether and how cultural and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 74 publications
(72 reference statements)
1
15
0
Order By: Relevance
“…Among them, distal stressors often refer to events, such as violence, and proximal factors usually refer to cognitive processes, self-regulation, etc. Negative thoughts will cause individuals to have negative perceptions and pessimistic interpretations when facing pressure ( Yu et al, 2022 ), which is a typical bad cognitive process. For LBC, both parents leave home all year-round, parental absence contributes to reduced or absent family resources, such as a lack of support and involvement ( Zhao et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, distal stressors often refer to events, such as violence, and proximal factors usually refer to cognitive processes, self-regulation, etc. Negative thoughts will cause individuals to have negative perceptions and pessimistic interpretations when facing pressure ( Yu et al, 2022 ), which is a typical bad cognitive process. For LBC, both parents leave home all year-round, parental absence contributes to reduced or absent family resources, such as a lack of support and involvement ( Zhao et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The comparison of activation patterns used three algorithms and consistently showed that the monetary loss network was more similar to the social pain network than to the physical pain network. For individuals, money is not only a physical stimulus but also has rich emotional and social meanings to people, since money can arouse positive or negative emotions (Tang, 1992 ; Yu, Huang, Mao, & Luo, 2022 ), elicit individuals’ internal motivation (Lea & Webley, 2006 ), reduce the harm caused by low self‐esteem (Zhang, 2009 ) and change the norms of interpersonal relationships (Vohs et al, 2008 ; Zaleskiewicz & Gasiorowska, 2016 ). Moreover, this result provided neural evidence of the social resource theory of money, in which money was regarded as a type of social resource, similar to social relationships, which might elicit pain and a sense of security (Zhou et al, 2009 ; Zhou & Gao, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…In specific, I intend to consider the several OXTR SNPs related to prosocial tendency and prosocial behaviors, which were demonstrated significantly in prior studies. For the sake of yielding reliable results, I will adopt a leave-one-out machine learning approach (Yu et al, 2020) to identify valid SNPs, which would interplay with subjective economic inequality to predict adolescents' prosocial behaviors.…”
Section: Contribution Of Oxytocin Gene Polymorphismsmentioning
confidence: 99%
“…Inspired by Yu et al's (2020) leave-one-out cross-validation, we employed the same approach to calculate polygenic scores (see figure 6). Participants were divided into test set After n iterations, we generated all participants' predicted prosocial behavior scores.…”
Section: Polygenic Leave-one-out Cross-validationmentioning
confidence: 99%
See 1 more Smart Citation